Trade and geography in the origins and spread of Islam - Stelios Michalopoulos; Alireza Naghavi; Giovanni Prarolo (Brown University, Department of Economics, 2012)
This research examines the economic origins and spread of Islam in the Old World and uncovers two empirical regularities. First, Muslim countries and ethnic groups exhibit highly unequal regional agricultural endowments. Second, Muslim adherence is systematically higher along the pre-Islamic trade routes. We discuss the possible mechanisms that may give rise to the observed pattern and provide a simple theoretical argument that highlights the interplay between an unequal geography and proximity to lucrative trade routes. We argue that these elements exacerbated inequalities across diverse tribal societies producing a conflictual environment that had the potential to disrupt trade flows. Any credible movement attempting to centralize these heterogeneous populations had to offer moral and economic rules addressing the underlying economic inequalities. Islam was such a movement. In line with this conjecture, we utilize anthropological information on precolonial traits of African ethnicities and show that Muslim groups have distinct economic, political, and societal arrangements featuring a subsistence pattern skewed towards animal husbandry, more equitable inheritance rules, and more politically centralized societies with a strong belief in a moralizing God.
Keywords: O10; O13; O16; O17; O18; F10; Z12; 330; Religion; Islam; Geography; Redistribution; Land Inequality; Africa; Wealth Inequality; Trade; Handelsgeschichte; Regionale Einkommensverteilung; Wirtschaftsgeographie; Islam; Einkommensumverteilung; Bodenreform; Welt